INCREASING TEACHERS' ABILITY IN USING LEARNING MEDIA AS A LEARNING SOURCE THROUGH TEACHER DISCUSSION IN ELEMENTARY SCHOOL - Biyanto (Literasi Nusantara, 2021)
The purpose of this study was to find out the efforts of teachers at SDN Carangwulung III, Wonosalam District, Jombang Regency in improving performance through the use of Learning Media media and find out whether discussions can improve teachers' abilities in using learning media media at Carangwulung III State Elementary School, Wonosalam District, Jombang Regency in 2016. This research activity is a form of action research. The subjects of this study were 11 elementary school teachers in the Carangwulung III State Elementary School, Wonosalam District, consisting of 8 PNS teachers, and 3 non-permanent teachers. Meanwhile, the object of research is the ability of teachers to use learning media. The research was conducted on teachers. The process of implementing the determination of the use of learning media through discussion to improve the ability of teachers in determining the use of learning media starts from initial supervision. There was an increase in the readiness of participants in discussion activities. The teachers gave a very positive response to the activity of determining the use of Learning Media through Discussion.